Hydrogen embrittlement susceptibility of 301 metastable austenitic stainless steel - Norouzi, Ehsan; Miresmaeili, Reza; Shahverdi, Hamid Reza; Askari-Paykani, Mohsen; Vergani, Laura Maria (Elsevier BV, 2025)
The influence of hydrogen on the mechanical properties and embrittlement behavior of 301 metastable austenitic stainless steel was studied. The hydrogen embrittlement (HE) was studied using in situ tensile testing under electrochemical hydrogen charging at various current densities. The results showed that the Portevin-LeChatelier (PLC) phenomenon occurred in the uncharged sample, whereas serration disappeared after hydrogen charging due to the hydrogen enhanced decohesion mechanism (HEDE) and the presence of alpha ' martensite. Hydrogen charging at current density of 10 and 30 mA/cm2 resulted in a 7 and 19 % loss in yield strength and a 77 and 80 % loss of elongation, respectively. The fracture toughness of uncharged and H precharged specimens was determined by the indentation technique and the results showed a 35 % decrease in fracture toughness after hydrogen charging. Evaluation of the microstructure by electron backscatter diffraction (EBSD) showed that the dislocation density increased in the presence of hydrogen. In addition, a reduction in stacking fault energy (SFE) by hydrogen resulted in the formation of more alpha ' martensite in the microstructure, compared to uncharged sample at the same level of deformation.